Gregg shorthand dictionary : a compilation of shorthand outlines for 34,055 words; 1,314 names; and 1,856 frequently used phrases - Gregg, John Robert; Leslie, Louis A.; Zoubek, Charles E. (New York : Gregg Pub. Division and McGraw-Hill, 1971)
The dictionary is divided into three parts: part one contains the shorthand outlines for 34,055 words; part two contains the shorthand outlines for 1,314 entries for personal and geographical names; and part three contains the shorthand outlines for 1,856 phrases frequently used in business dictation.
Shorthand written by Charles Rader.
ne 01/09/2021
Ref.
Keywords: Shorthand